2012
DOI: 10.1007/s12040-012-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of the Late Neogene Siwalik sandstone, Kumaun Himalayan Foreland Basin: Constraints from the metamorphic rank and index of detrital rock fragments

Abstract: An understanding about lithology, tectonics and unroofing history of provenance is mostly drawn from the compositional and textural parameters of the detrital fragments. We here use different metamorphic ranks (Rm) and metamorphic index (MI) values of rock fragments present in Late Neogene Siwalik sandstone of the Ramganga sub-basin to infer the provenance history. The study indicates maximum contribution from metamorphic ranks 1 and 2 (Rm1 and Rm2; meta-sedimentary and very low grade metamorphic rocks) and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Figure shows QtFL petrofacies compositional fields of the Middle Siwalik sandstones of Potwar Plateau, Pakistan (Critelli & Ingersoll, ); Ramnagar, Kumaun (Tandon, ); Ranibag‐Jeolikot, Kumaun (this study); Baliya River section, Kumaun (Jalal & Ghosh, ); Western Nepal (four section between west of Karnali River and Surai Khola; DeCelles et al, ); Karnali River section, Nepal (Sigdel & Sakai, ); Surai Khola section, Nepal (Critelli & Ingersoll, ); Bakiya Khola section, Nepal (Critelli & Ingersoll, ); Muksar Khola section, Nepal (Chirouze et al, ); Koshi River Section, Nepal (Baral et al, ), Tista valley, eastern India (Kundu et al, ); and Lish River section, eastern India (Kundu et al, ). The sandstones of the Potwar Plateau, representing the western part of the foreland basin, are slightly depleted in quartz and enriched in feldspar as compared with sandstones from the rest of the central and eastern parts of the basin.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Figure shows QtFL petrofacies compositional fields of the Middle Siwalik sandstones of Potwar Plateau, Pakistan (Critelli & Ingersoll, ); Ramnagar, Kumaun (Tandon, ); Ranibag‐Jeolikot, Kumaun (this study); Baliya River section, Kumaun (Jalal & Ghosh, ); Western Nepal (four section between west of Karnali River and Surai Khola; DeCelles et al, ); Karnali River section, Nepal (Sigdel & Sakai, ); Surai Khola section, Nepal (Critelli & Ingersoll, ); Bakiya Khola section, Nepal (Critelli & Ingersoll, ); Muksar Khola section, Nepal (Chirouze et al, ); Koshi River Section, Nepal (Baral et al, ), Tista valley, eastern India (Kundu et al, ); and Lish River section, eastern India (Kundu et al, ). The sandstones of the Potwar Plateau, representing the western part of the foreland basin, are slightly depleted in quartz and enriched in feldspar as compared with sandstones from the rest of the central and eastern parts of the basin.…”
Section: Discussionmentioning
confidence: 75%
“…Given the absence of any evidences of deposition from a contemporaneously existing large axial river systems, like Indus, Ganga or Brahmaputra (Taral & Chakraborty, ), it is likely that the exposed Middle Siwalik sequences were deposited only to the orogen‐ward side of the axial river systems and thus did not receive sediments from the peninsular India. Conforming to this presumption, the previous studies have determined that the Middle Siwalik sediments in different parts of the foreland basin were supplied exclusively from the Himalayan hinterlands (Baral et al, , ; Critelli & Ingersoll, ; Chirouze et al, ; Jalal & Ghosh, ; Kundu et al, ; 2016; Sigdel & Sakai, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar result was obtained by White et al (2002) from the study of early Middle Miocene Molasse deposit in northern India. In Kumaun Himalaya, Jalal and Ghosh (2012) found that at ~7.7-4.5 Ma, metamorphic rocks of LH acted as a dominant source of the Siwalik Group that gradually changes to low-grade metamorphic rocks of LH (Janusar Group) after the reactivation of MBT at ~5.5 Ma. In the eastern Himalaya, Higher Himalaya acted as a prominent source of sediment between 13-7 and <2.6 Ma, while in between ca.…”
Section: Provenance Of Siwalik Group Along the Other Part Of The Himamentioning
confidence: 99%